IL-7 Promotes the Expansion of Circulating CD28- Cytotoxic T Lymphocytes in Patients With IgG4-Related Disease via the JAK Signaling - Xia, Chang-sheng; Long, Yan; Liu, Yanying; Alifu, Aikede; Zeng, Xingyue; Liu, Chen (Frontiers in Immunology, 2022)
Objectives: This study aimed to elucidate the changes and associated mechanisms of circulating CD28- cytotoxic T lymphocytes (CTLs) in patients with IgG4-related disease (IgG4-RD). Methods: Fifty IgG4-RD patients and 15 healthy controls (HCs) were recruited. Peripheral blood mononuclear cells (PBMCs) were isolated, and the levels of circulating CD28- CTLs were detected by flow cytometry, and the proportions of CD127 negative or granzyme B (GZMB) positive CD28- CTL subsets were analyzed in the meantime. Mechanistically, PBMCs isolated from IgG4-RD patients were stimulated with IL-7 in the presence or absence of the JAK inhibitor tofacitinib. Flow cytometry was used to analyze the proliferation of CD28- CTLs and the changes in related subpopulations. Results: Circulating CD4+CD28- CTLs and CD8+CD28- CTLs were significantly increased in IgG4-RD patients compared with HCs, accompanied by an upregulation of CD127- or GZMB+ CTL subsets. The ex vivo culture of PBMCs showed that IL-7 could induce the amplification of CD4+CD28- CTLs and CD8+CD28- CTLs in IgG4-RD. Furthermore, IL-7 promotes the proliferation and functional subset changes of these CD28- CTLs in this disease. The selective JAK inhibitor tofacitinib significantly inhibited the effects of IL-7 on CD4+CD28- CTLs and CD8+CD28- CTLs. Conclusion: IL-7 can affect the immune balance of IgG4-RD patients by promoting the expansion and function of CD4+CD28- and CD8+CD28- CTLs in IgG4-RD through the JAK pathway. Blockade of the IL-7 signaling pathway may be a new therapeutic strategy for IgG4-RD.